A clinical and experimental overview of sirenomelia: insight into the mechanisms of congenital limb malformations - Carlos Garrido-Allepuz; Endika Haro; Domingo González-Lamuño; María Luisa Martínez-Frías; Federica Bertocchini; Maria A. Ros (The Company of Biologists, 2011)
Sirenomelia, also known as sirenomelia sequence, is a severe malformation of the lower body characterized by fusion of the legs and a variable combination of visceral abnormalities. The causes of this malformation remain unknown, although the discovery that it can have a genetic basis in mice represents an important step towards the understanding of its pathogenesis. Sirenomelia occurs in mice lacking Cyp26a1, an enzyme that degrades retinoic acid (RA), and in mice that develop with reduced bone morphogenetic protein (Bmp) signaling in the caudal embryonic region. The phenotypes of these mutant mice suggest that sirenomelia in humans is associated with an excess of RA signaling and a deficit in Bmp signaling in the caudal body. Clinical studies of sirenomelia have given rise to two main pathogenic hypotheses. The first hypothesis, based on the aberrant abdominal and umbilical vascular pattern of affected individuals, postulates a primary vascular defect that leaves the caudal part of the embryo hypoperfused. The second hypothesis, based on the overall malformation of the caudal body, postulates a primary defect in the generation of the mesoderm. This review gathers experimental and clinical information on sirenomelia together with the necessary background to understand how deviations from normal development of the caudal part of the embryo might lead to this multisystemic malformation.